First interactive solar & wind energy atlas for northeast Mexico - Fernando Gustavo Lappe Mansilla (2014)
Due to the fact that Mexico has over 71,000 MW of potential renewable energy installed capacity and that as of today there are only around 12,000 MW installed (Mexican Energy Ministry, 2013) (barely 17% of the total), it was decided to investigate the potential causes of this situation with the goal of contributing to the promotion of development of renewable energy projects and the exploitation of said potential. During this analysis it was found that the National Weather Ministry of Mexico has only 188 weather stations that are managed by the National Board of that Ministry (there are over 406 more but are managed by other private/public bodies), which means that there are very wide regions across the whole Mexican territory where the weather conditions (wind speed and solar irradiance) are not known. This is considered to be one of the different factors that impede and obstruct the development of big scale renewable energy projects in that country, prohibiting also the establishment of a turning point towards a more green and environmental friendly way of producing electricity. For this project, 7 States in Mexico (803,097 km2) have been analyzed. Each one of those 354 municipalities has been divided into 100 km2 squares. For each centroid of those squares the yearly mean wind speed and solar irradiance conditions were calculated for the period 2008-2012. The distances to the next transmission line (400 and/ or 230 kV) and next highway (or accessible road) were also calculated. Therefore, two methods of spatial interpolation were compared to determine their suitability for estimating the yearly mean wind speeds and solar irradiance for the Northeast States of Mexico (Tamaulipas, Nuevo Leon, Coahuila, Chihuahua, Durango, Zacatecas and San Luis Potosi), from data recorded at nearly 90 locations across the mentioned region (for calculation purposes, surrounding States were also considered Aguascalientes, Guanajuato, Hidalgo, Jalisco, Nayarit, Queretaro, Sinaloa, Sonora and Veracruz). The eventual purpose of producing such surfaces was to help estimate, identify and recognize the areas with the best conditions for developing big scale renewable energy projects, meaning the ones with the most favorable environmental conditions, the ones closer to highways and to transmission lines. The interpolation techniques included two local, exact and deterministic methods: Inverse Distance Weighting (IDW) and Triangulated Irregular Network (TIN). Quantitative assessment of the continuous surfaces showed that there was a large difference between the accuracy of interpolation methods used, being IDW the most suitable for the analyzed region. The results of that method were used for the further construction of the First Interactive Solar &Wind Energy Atlas for Northeast Mexico.
Keywords: Mexico; Atlas; Wind energy; solar energy